Waste Management by Transformation of Recovered Silver from Electronic and Laboratory Wastes into Silver Nitrate Reagent - กัณณะ, มิกิ; สมนาม, สราวุฒิ (KKU Science Journal, 2022)
This research has proposed waste management of electronic and laboratory wastes by recovering the silver mold using chemical process and turning it into silver nitrate reagent for use in laboratory. The studied electronic waste which was plastic circuit board inside a keyboard (KB) and compact disc (CD), while the laboratory wastes were the waste solution of silver ion (Ag+) and silver chloride (AgCl) precipitate. From this study, the suitable conditions to recover silver element from KB and CD were the extraction with 1M HNO3 at 60oC for 6 hrs. (for KB) and 4 hrs. (for CD) the ratio between KB and CD to HNO3 at 1:20 and 1:5, respectively. The silver contents in KB and CD equal to 0.19% and 0.018%, respectively. Silver ion (Ag+) was recovered from AgCl precipitate by dissolving with conc.NH3. The Ag+ which was extracted from AgCl and the left over solution of Ag+ was reduced by the copper wire cemented to the metallic silver with the purity level over 91.0%. The recovered silver was need to prepare AgNO3 reagent for determination of chloride in the salt and water samples, and used as the Tollen’s reagent for qualitative analysis of organic substances. It was found that the prepared AgNO3 had the same quality as the commercial products in the market. Moreover, cost of this reagent obtained from the proposed process is 90% lower than using the commercial products. Hence, this research could be the guidelines of waste management for other Ag containing wastes in order to reduce the amount of chemical waste and expense in laboratory.